Understanding Radicalists and Fundamentalist Islamic Groups in Indonesia: Ideology and Model of Movement - Faiq, Muhammad (Tasamuh: Jurnal Studi Islam, 2021)
Abstract: Since the Reformation Era, various Islamic organizations or groups have emerged in Indonesia with different ideologies and movement models, such as Hizbut Tahrir Indonesia (HTI), the Indonesian Mujahidin Council (MMI), the Indonesian Muslim Brotherhood, the Islamic Defenders Front (FPI), and Jemaah Islamiyah. Most Indonesian Muslims do not warmly welcome their presence as the spirit of their struggle is not appropriate with the character and culture of the Indonesian people. They often use violence and even terror in struggling for Islam with the reason of amr ma’ruf nahi munkar (enjoining good and forbidding evil). So it is not surprising that the government recently dissolved the HTI and FPI. By using a qualitative approach, this study aims to uncover their ideology and movement model and the ideologies that influence them. From the data obtained from various related literature such as textbooks, journals, and the web, this study finds that these Islamic groups are ideologically influenced by trans-national Islamic groups with fundamentalism and even radicalism characters. They disagree with the Indonesian government system, which is considered secular and incompatible with Islamic values. They often use violence and terror to enforce Islamic shari'ah and even change the NKRI system with the system of Khilafat Islamiyah (Islamic caliphate). Keywords: Radicalist, fundamentalist, Islamic caliphate, shari'ah. Abstrak: Sejak Era Reformasi, berbagai ormas atau kelompok Islam bermunculan di Indonesia dengan ideologi dan model gerakan yang berbeda, seperti Hizbut Tahrir Indonesia (HTI), Majelis Mujahidin Indonesia (MMI), Ikhwanul Muslimin Indonesia, Front Pembela Islam (FPI), dan Jemaah Islamiyah. Sebagian besar umat Islam Indonesia tidak menyambut baik kehadiran mereka karena semangat perjuangan mereka tidak sesuai dengan karakter dan budaya masyarakat Indonesia. Mereka sering menggunakan kekerasan bahkan teror dalam memperjuangkan Islam dengan dalih amr ma'ruf nahi munkar. Maka tidak heran jika belakangan ini organisasi tersebut, khususnya HTI dan FPI, dibubarkan oleh pemerintah. Dengan menggunakan pendekatan kualitatif, penelitian ini bertujuan untuk mengungkap ideologi dan model gerakan mereka serta ideologi yang mempengaruhinya. Dari data yang diperoleh dari berbagai literatur terkait seperti buku teks, jurnal, dan web, penelitian ini menemukan bahwa kelompok-kelompok Islam tersebut secara ideologis dipengaruhi oleh kelompok-kelompok Islam transnasional dengan karakter fundamentalisme bahkan radikalisme. Mereka tidak setuju dengan sistem pemerintahan Indonesia yang dianggap sekuler dan bertentangan dengan nilai-nilai Islam. Mereka kerap menggunakan kekerasan dan teror untuk menegakkan syari'at Islam bahkan mengubah bentuk NKRI (Negara Kesatuan Republik Indonesia) dengan sistem Khilafah Islamiyah. Kata kunci: Radikalisme, fundamentalisme, khilafah Islamiyah, syari'at Islam.